PENGEMBANGAN PENDIDIKAN KEWIRAUSAHAAN BERBASIS PENDIDIKAN KARAKTER DI SMA NEGERI 1 TANJUNG RAJA - Sarina, Sarina; Lian, Bukman (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2018)
In this paper, we tried to see the entrepreneurship character education of SMA Negeri 1 Tanjung Raja. We raised character-based entrepreneurship education. We used qualitative in this paper and interviews, observations, document studies and triangulation were used to collect the data. The results provided indicate that the development of entrepreneurship education in SMA Negeri 1 Tanjung Raja were religious, noble character, national competitiveness, creative, independent, discipline and environmentally insight.